Comparing Cathelicidin Susceptibility of the Meningitis Pathogens Streptococcus suis and Escherichia coli in Culture Medium in Contrast to Porcine or Human Cerebrospinal Fluid - Meurer, Marita; de Buhr, Nicole; Unger, Linn Meret; Bonilla, Marta C.; Seele, Jana; Nau, Roland; Baums, Christoph G.; Gutsmann, Thomas; Schwarz, Stefan; von Köckritz-Blickwede, Maren (Frontiers in Microbiology, 2020)
Host defense peptides or antimicrobial peptides (AMPs), e.g., cathelicidins, have recently been discussed as a potential new treatment option against bacterial infections. To test the efficacy of AMPs, standardized methods that closely mimic the physiological conditions at the site of infection are still needed. The aim of our study was to test the meningitis causing bacteria S. suis and E. coli for their susceptibility to cathelicidins in culture medium versus cerebrospinal fluid (CSF). Suscepti-bility testing was performed in analogy to the broth microdilution method described by the Clinical and Laboratory Standard Institute (CLSI) to determine minimal inhibitory concen-trations (MICs) of antimicrobial agents. MICs were determined using cation-adjusted Mueller-Hinton broth (CA-MHB), Lysogeny broth (LB), Roswell Park Memorial Institute medium (RPMI) or Dulbecco's Modified Eagle's Medium (DMEM) (the latter two supple-mented with 5% CA-MHB or blood) and compared with MICs obtained in porcine or human CSF. Our data showed that MICs obtained in CA-MHB as recommended by CLSI do not reflect the MICs obtained in the physiological body fluid CSF. However, the MICs of clinical iso-lates of S. suis tested in RPMI medium supplemented with CA-MHB, were similar to those of the same strains tested in CSF. In contrast, the MICs in the human CSF for the tested E. coli K1 strain were higher compared to the RPMI medium and showed even higher values than in CA-MHB. This highlights the need for susceptibility testing of AMPs in a medium that closely mimics the clinically relevant conditions.